Feedback of the third interlaboratory exercise organised on wheat in the framework of the OBT working group. (January 2018) - Baglan, N.; Cossonnet, C.; Roche, E.; Kim, S.B.; Croudace, I.; Warwick, P.
Abstract: Organically bound tritium (OBT) has become of increasing interest within the last decade, with a focus on its behaviour and also its analysis, which are both important to assess tritium distribution in the environment and dose consequences. After the first OBT International Workshop which was held in France in May 2012, an international working group was created. The expected benefits are the following: remove or reduce uncertainty in OBT analysis results, provide better OBT model validation data and better public dose results, increase the number of potential measuring OBT laboratories, validate all of the stages of the procedures based on a larger population and more statistically significant results, and investigate the feasibility of CRM's and RM's production. In this framework, three OBT exercises were organised; the 1st one on potatoes was conducted in 2013 by the Canadian National Laboratories (former AECL) with about 20 participating labs from around the world, the 2nd one on a sediment was organised in 2014 by GAU Radioanalytical (University of Southampton) on a sediment with again about 20 participating labs and the third one on wheat was organised in 2015 by the Commissariat à l'énergie atomique (CEA) with about 25 participating labs. Highlights: An OBT exercise with low activity concentration levels (below 100 Bq·L −1 in combustion water). The confirmation of tritium lab analytical skills for OBT determination. The first steps toward the preparation of reference materials.